Evaluating Industrial Dispute Resolution Methods: A Case Study of Bangladesh - Shafiul Alam, S. M.; Chaity, Naznin Sultana (European Scientific Journal, ESJ, 2024)
Currently, parties involved in the process of industrial dispute resolution prefer alternative dispute resolution (ADR) to the adversarial process which requires an evaluation of ADR to infer how effective it is. Theoretically, the concept of ADR has been originated from the theory of conflict resolution management. Even though ADR has been implemented largely by apparel firms, studies to assess the effectiveness of ADR are scant. To assess the effectiveness of ADR as an industrial dispute resolution method (DRM), the study evaluated seven hypotheses using the Chi-square test and Cramer’s V. Data were gathered from both employers and employees of apparel factories in Bangladesh using two different sets of survey questionnaires. The results showed that employees are more familiar with ADR processes if the companies are run for a long time. It has also been found that the presence of a labor union has been determined to be crucial in the selection of DRMs and workers advocate more for ADR than formal adjudication machinery. The findings of the research are expected to contribute to the dispute resolution process since this study attempted to explore the perceptions of both employees and employers which is instrumental to the amicable settlement of disputes by applying ADR.